The Use of Plastic Fiber for Minimizing Stripping Potential of Bituminous Mixture - Usman, Nura; Mohd Masirin, Mohd Idrus; Ahmad, Kabiru Abdullahi; Nda, Muhammad (International Journal of Integrated Engineering, 2019)
One of the effects of water in bituminous pavement is the stripping of aggregates from the mixture causing severe distresses such as potholes. In this study, fiber was produced using recycle plastics and it was used as reinforcement in bituminous mixture against moisture damage. The reinforcements were 0.3%, 0.5% 0.7% and 1.0% of the total weight of bituminous mixture with a view to determine the effective fiber dosage. The stripping potential of control and fiber reinforced mixtures were determined using moisture susceptibility test. From the test results, highest tensile strength ratio (TSR) was obtained in mixtures containing 0.5% recycle plastic fiber. The result also indicated higher indirect tensile strength for both dry and saturated at 0.5% plastic fiber reinforcement. For 0.7% and 1.0% recycle plastic fiber reinforced bituminous mixture, both tensile strength and tensile strength ratio were low compared to that of control mixture. From this study, reinforcing bituminous mixture using 0.5% recycle plastic proved to be effective in improving stripping resistance.